2018
DOI: 10.21276/obgyn.2018.5.1.6
|View full text |Cite
|
Sign up to set email alerts
|

A study on maternal and perinatal outcome of abruptio placentae in a tertiary centre

Abstract: Objective: The study was aimed to find out the incidence, obstetric risk factors, and various complications of abruptio placentae and to analyze the maternal and perinatal outcome of the same. Materials and Methods: It was a hospital based observational study for a period of one year carried out from 1 st June 2012 to 31 st May 2013. Study population included all pregnancy cases of gestational age of 28 weeks onwards having sign and symptoms of abruptio placentae. Results: Out of 15111 deliveries there were 70… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 5 publications
0
1
0
Order By: Relevance
“…Some studies reported that association of anemia was 51.4% cases of abruption placentae. 13 Ultrasonographic findings in patients with PA show variabilities depending on the time of abruption, site of abruption, and the location of placenta. 14 In the present study, the majority (94.74%) of abruptio placentae are USG undiagnosed cases probably due to its sudden occurrence and requiring immediate delivery of the fetus.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies reported that association of anemia was 51.4% cases of abruption placentae. 13 Ultrasonographic findings in patients with PA show variabilities depending on the time of abruption, site of abruption, and the location of placenta. 14 In the present study, the majority (94.74%) of abruptio placentae are USG undiagnosed cases probably due to its sudden occurrence and requiring immediate delivery of the fetus.…”
Section: Discussionmentioning
confidence: 99%